Period 2 Regulates CYP2B10 Expression and Activity in Mouse Liver - MengLin Chen (Frontiers Media S.A., 2021)
CYP2B10 is responsible for metabolism and detoxification of many clinical drugs. Here, we aimed to investigate a potential role of Period 2 (PER2) in regulating expression of hepatic CYP2B10. Regulatory effects of PER2 on hepatic expression of CYP2B10 and other enzymes were determined using Per2-deficient mice with exons 4-6 deleted (named Per2Del4-6 mice). In vitro and in vivo metabolic activities of CYP2B10 were probed using cyclophosphamide (CPA) as a specific substrate. Regulatory mechanism was investigated using luciferase reporter assays. Genotyping and Western blotting demonstrated loss of wild-type Per2 transcript and markedly reduced PER2 protein in Per2Del4-6 mice. Hepatic expression of a plenty of drug-metabolizing genes (including Cyp2a4/2a5, Cyp2b10, Ugt1a1, Ugt1a9, Ugt2b36, Sult1a1 and Sult1e1) were altered (and majority were down-regulated) in Per2Del4-6 mice. Of note, Cyp2b10, Ugt1a9 and Sult1a1 were three genes considerably affected with reduced expression. Decreased expression of CYP2B10 was translated to reduced metabolism and altered pharmacokinetics of CPA as well as attenuated CPA hepatotoxicity in Per2Del4-6 mice. Positive regulation of CYP2B10 by PER2 was further confirmed in both Hepa-1c1c7 and AML-12 cells. Based on luciferase reporter assays, it was shown that PER2 regulated Cyp2b10 transcription in a REV-ERBα-dependent manner. REV-ERBα was negatively regulated by PER2 (increased REV-ERBα expression in Per2Del4-6 mice) and itself was also a repressor of CYP2B10. In conclusion, PER2 positively regulates CYP2B10 expression and activity in mouse liver through inhibiting its repressor REV-ERBα.